Efficacy and safety of aripiprazole lauroxil once-monthly versus aripiprazole once-monthly long-acting injectable formulations in patients with acute symptoms of schizophrenia: an indirect comparison of two double-blind placebo-controlled studies. (3rd April 2018) - Cameron, Chris; Zummo, Jacqueline; Desai, Dharmik; Drake, Christine; Hutton, Brian; Kotb, Ahmed; Weiden, Peter J.
Abstract: Background: Aripiprazole lauroxil (AL) is a long-acting injectable atypical antipsychotic recently approved for the treatment of schizophrenia. Objective: To indirectly compare the safety and efficacy of AL and aripiprazole once-monthly (AOM). Methods: A systematic search was performed to identify randomized, controlled trials of AOM and AL that met criteria for indirect comparison according to Bayesian network meta-analysis. The analysis indirectly compared AL and AOM treatment groups for efficacy by mean change in Positive and Negative Syndrome Scale (PANSS) total score and ≥30% reduction in PANSS total score, as well as tolerability including adverse events, akathisia, and weight gain. Results: Two studies were selected, resulting in three active-treatment groups: AL 441 mg, AL 882 mg, and AOM 400 mg. All active treatments were efficacious compared with placebo. There were no differences in indirect comparisons of akathisia. All three groups showed some weight gain, but only the AOM 400 mg group was significantly greater than placebo. Conclusions: Results of this indirect comparison found that both doses of AL and the single AOM dose were therapeutic and efficacious for the treatment of schizophrenia with a similar safety profile.